Electricity markets are broken – can they be fixed? - Keay, M (Oxford Institute for Energy Studies, 2016)
This paper argues that electricity markets in Europe are broken. The increasing penetration of subsidised, zero marginal cost, intermittent generation has distorted prices to the extent that they can no longer give effective signals for investment or operation. The problem is increasingly being recognised but there is no consensus on the solution. The paper considers a number of options; it concludes that a serious debate needs to get under way now if we are to develop sustainable markets for a low carbon future.